The Role Of The Macroprudential Intermediation Ratio And The Countercyclical Capital Buffer In Maintaining Indonesia’S Financial System Stability - Asa Puspa Nusantari; Evina Verintina; Dewi Mulyaningtyas; Shandy Syah Putra Elyustomo (Asosiasi Dosen Muda Indonesia, 2026)
Financial system stability is a crucial element for the sustainability of the national economy. Imbalances in the financial sector, particularly those arising from credit growth that is not aligned with economic capacity, can lead to systemic risk. In response to these risks, Bank Indonesia has implemented macroprudential policies through instruments such as the Macroprudential Intermediation Ratio (RIM) and the Countercyclical Capital Buffer (CCyB). This study aims to analyze how RIM and CCyB contribute to maintaining financial system stability in Indonesia by utilizing national data from 2010 to 2024. Financial system stability is measured using the Non-Performing Loan (NPL) ratio in the banking sector. The analytical method employed is time series regression using the Ordinary Least Squares (OLS) approach, complemented by stationarity tests and classical assumption tests. The results indicate that RIM has a significant negative effect on NPL, while CCyB also exhibits a negative relationship, although with a lower level of significance. These findings suggest that synergy in macroprudential policies is essential to strengthen banking sector resilience and maintain the stability of Indonesia’s financial system.